2020
DOI: 10.1017/s2045796020000438
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the onset of major depressive disorder in adults with type 2 diabetes living in 12 different countries: results from the INTERPRET-DD prospective study

Abstract: Aims To examine the factors that are associated with changes in depression in people with type 2 diabetes living in 12 different countries. Methods People with type 2 diabetes treated in out-patient settings aged 18–65 years underwent a psychiatric assessment to diagnose major depressive disorder (MDD) at baseline and follow-up. At both time points, participants completed the Patient Health Questionnaire (PHQ-9), the WHO five-item Well-being scale (WHO-5) and the Problem Areas in Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 38 publications
0
22
0
4
Order By: Relevance
“…This information is consistent with previous data about the higher prevalence of depressive, anxiety, and eating disorders in females compared with males in the general population. Several studies, 3 , 37–39 including a collaborative study in 14 countries reported that among T2D patients, women had increased odds of major depressive disorder than men (OR=1.96). 37 Also, a systematic literature review identified a different prevalence of BED according to sex (0–9.8% for women and 0–0.5%for men).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This information is consistent with previous data about the higher prevalence of depressive, anxiety, and eating disorders in females compared with males in the general population. Several studies, 3 , 37–39 including a collaborative study in 14 countries reported that among T2D patients, women had increased odds of major depressive disorder than men (OR=1.96). 37 Also, a systematic literature review identified a different prevalence of BED according to sex (0–9.8% for women and 0–0.5%for men).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies, 3 , 37–39 including a collaborative study in 14 countries reported that among T2D patients, women had increased odds of major depressive disorder than men (OR=1.96). 37 Also, a systematic literature review identified a different prevalence of BED according to sex (0–9.8% for women and 0–0.5%for men). 36 …”
Section: Discussionmentioning
confidence: 99%
“…Diabetes distress, the psychological burden caused by dealing with having diabetes and having to care for it, has indeed been linked to depression 31 . However, a large international longitudinal study of 14 countries has shown that only depressive symptoms rather than MDD were predicted by diabetes distress one year after diagnosis 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Another 11-year cohort study examining risk factors for depression in type 2 diabetic patients (N = 50 590) suggests that depression is strongly associated with severity of disease progression, regardless of other potential covariates such as demographic status, comorbidities, or medication compliance (43). A multicentre European study carried out in 12 countries with type 2 diabetic patients also found that being female and less physically active significantly increases the risk of having major depressive disorder (44). Finally, a cohort study with 3240 patients suggested that being female and younger are risk factors for clinical depression associated with diabetes (45).…”
Section: Diabetesmentioning
confidence: 99%